Outcomes of Multiple Runs of Extracorporeal Membrane Oxygenation: An analysis of the Extracorporeal Life Support Registry. (February 2022) - Cooper, David S.; Thiagarajan, Ravi; Henry, Brandon Michael; Byrnes, Jonathan W.; Misfeldt, Andrew; Frischer, Jason; King, Eileen; Gao, Zhiqian; Rycus, Peter; Marino, Bradley S.
Objective: When patients deteriorate after decannulation from extracorporeal membrane oxygenation (ECMO), a second run of extracorporeal support may be considered. However, repeat cannulation can be difficult and poor outcomes associated with multiple ECMO runs are a concern. The aim of this study was to evaluate outcomes and identify factors associated with survival and mortality in cases of multiple runs of extracorporeal membrane oxygenation. Design: Retrospective cohort analysis of the Extracorporeal Life Support Organization Registry. Setting: The Extracorporeal Life Support Organization's registry was queried for neonates, children, and adults receiving 2 or more runs of ECMO during the same hospitalization, for any indication, from 1998 to 2015. Patients: 1, 818 patients from the Extracorporeal Life Support Organization Registry. Results: Of the 1, 818 patients, 1, 648 underwent 2 runs and 170 underwent 3 or more runs of ECMO. The survival to discharge rate was 36.7% for 2 runs and 29.4% for 3 or more runs. No significant differences in survival were detected in analysis by decade of ECMO run (p = 0.21). Pediatric patients had less mortality than adults (OR: 0.45, 95%CI: 0.24-0.82). Cardiac support on the first run portrayed worse mortality than pulmonary support regardless of final run indication (OR:1.38, 95%CI: 1.09-1.75). Across all age groups, patients receiving pulmonary support on the last run tended to have higher survival rates regardless of support type on the first run. The only first run complication independently predictive of mortality on the final run was renal complications (OR: 1.60, 95%CI: 1.28-1.99). Conclusions: Though the use of multiple runs of ECMO is growing, outcomes remain poor for most cohorts. Survival decreases with each additional run. Patients requiring additional runs for a pulmonary indication should be considered prime candidates. Renal complications on the first run significantly increases the risk of mortality on subsequent runs, and as such, careful consideration should be applied in these cases.